MENCIPTAKAN CUSTOMER EXPERIENCE MENGGUNAKAN MERK - Benedicta Evienia Prabawanti (Bina Ekonomi, 2006)
The most brand theory defines brand as identifies only and differentiate one product from another. That means the brand is identity of product that signify ownership and guarantee quality. This paradigm about brand misses the very essences of a brand as rich of sensory, affective, and cognitive associations that result of memorable and rewarding brand experience. The brand experience increases the value of product in customer mind. The Manning Selvage & Lee, a research firm, find that brand leader do not just have memorable name and great image-they also deliver experience. This paper focus on how brand experience can be created by the firm.